2016
DOI: 10.3168/jds.2015-10025
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Inhibitory activities of the lantibiotic nisin combined with phenolic compounds against Staphylococcus aureus and Listeria monocytogenes in cow milk

Abstract: We aimed to investigate the antibacterial activities of carvacrol, thymol, eugenol, cinnamaldehyde, and lantibiotic nisin against standard bacterial strains of the milk pathogens Staphylococcus aureus ATCC 25923 and Listeria monocytogenes ATCC 15313 in cow milk. The minimum inhibitory concentrations (MIC) of these substances were recorded. The synergistic effects were also assessed in culture medium (time kill curve) and in a food model (cow milk) during the storage period (4 °C for 6 d) after inoculation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 33 publications
(35 reference statements)
4
23
0
Order By: Relevance
“…for this reason, in this study we investigate the combined antilisterial activity of CA, nisin and barberry extract in dual combinations to discover possible synergistic effects. Researchers investigated antibacterial activity of nisin and reported 125 µg/ml as MIC value of nisin against L. monocytogenes which is in agreement with the result of our study (8). The antibacterial effects of nisin were indicated against gram-positive food borne bacteria such as Staphylococcus aureus and L. monocytogenes (28).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…for this reason, in this study we investigate the combined antilisterial activity of CA, nisin and barberry extract in dual combinations to discover possible synergistic effects. Researchers investigated antibacterial activity of nisin and reported 125 µg/ml as MIC value of nisin against L. monocytogenes which is in agreement with the result of our study (8). The antibacterial effects of nisin were indicated against gram-positive food borne bacteria such as Staphylococcus aureus and L. monocytogenes (28).…”
Section: Discussionsupporting
confidence: 89%
“…For CA, the MIC value against L. monocytogenes was 0.312 µl/ml. In another study, MIC value of CA against L. monocytogenes was 65 µg/ml (8). Other researchers indicated that MIC value of CA against S. aureus was 0.31 mg/ml (33), and 1.56 µl/ml (~0.26 mg/ml) (11), which were similar to that calculated in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, considerable work has been conducted to enhance the poor antibacterial activity of nisin toward Gram-negative bacteria (due to the outer membrane of the Gram-negative cell wall that acts as a physical barrier, obstructing access of the peptides to the cytoplasmic membrane). Such strategies have included destabilization of the outer membrane by combining with essential oils that contain aldehydes, terpenes and phenolic compounds [ 26 , 27 ]. Other strategies have involved nisin and chelating agents such as EDTA, which acts by removing Mg 2+ and Ca 2+ ions essential for stabilizing the lipopolysaccharide (LPS) outer membrane of Gram-negative bacteria [ 18 , 28 ].…”
Section: Discussionmentioning
confidence: 99%